Legal Regulation Regarding European Citizens’ Initiative - Yocheva, Katerina (Yearbook of the Law Department, 2019)
The paper is dedicated to analysis of the legal regulation regarding the European Citizens’ Initiative, which is part of the relevant EU law (primary and secondary EU law), as well as regarding the respective relevant provisions stemming from the national legislation of the Republic of Bulgaria.